ANALYSIS OF THE EFFECTIVENESS OF RAW MATERIAL WAREHOUSE MANAGEMENT AT PT INDONESIA ASAHAN ALUMINUM - Ericson Chandra; Nazaruddin; Meilita Tryana Sembiring (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Research Objectives To find out the raw material management process carried out at PT Indonesia Asahan Aluminum, to find outwhether the current raw material storage layout is effective or not and to find out what can be done or improved to increase the effectiveness of raw material warehouse management at PT Indonesia Asahan Aluminum. The type of research used is quantitative descriptive research. This research was conducted at PT Indonesia Asahan Aluminum. Based on the results of the analysis that has been carried out on the implementation of the class-based storage method in the PT Indonesia Asahan Aluminum warehouse, namely the Potential for Increasing Operational Efficiency: The calculation results show that by implementing the class-based storage method, there is the potential for a significant increase in efficiency. Projections show a reduction in the total distance traveled by 630,441 meters or around 28%, which shows that this method can minimize the distance traveled for picking up raw materials, thereby speeding up the process of searching for and retrieving goods. Better Grouping of Raw Materials: The class-based storage method allows grouping of raw materials based on frequency of use and raw material characteristics. This grouping can help in organizing the warehouse layout more efficiently, where frequently used raw materials are placed closer to the picking area, while rarely used raw materials are placed further away but still well organized. Optimizing Space Use: Projections for implementing the class-based storage method show the potential for more optimal use of storage space. By organizing raw materials based on class, each storage space can be used more efficiently, reducing unnecessary buildup or emptiness. Process Time Reduction: Reducing travel distance is also expected to have an impact on reducing the time required for the process of searching for and retrieving raw materials. This has the potential to increase employee productivity and speed up workflow in the warehouse.